Phytochemical analysis and antioxidant defense of kiwifruit (Actinidia deliciosa) against pancreatic cancer and AAPH-induced RBCs hemolysis - EL AZAB,Eman Fawzy (2022)
Abstract Kiwifruit (Actinidia deliciosa) is a superb nutritional source of phenolic compounds that are beneficial in the prevention of different diseases. The main goal of the current study was to estimate the oxidative activity and compare the effect of the ethanol extract of this fruit's peel and flesh on pancreatic cancer against pancreatic cancer and in vitro 2, 2-azobis-2-amidinopropane dihydrochloride (AAPH) erythrocytes hemolytic oxidative damage. Firstly, HPLC was utilized to identify the phenolic compounds in each extract that showed that p-coumaric acid & ferulic acid (in the peel), syringic acid & cinnamic acid (in the flesh) were the most abundant. Concerning the anti-cancer effect, flesh extract exhibited more cytotoxic impact as detected by the reduction of PANC-1 cell line viability with IC50 of 232.89 µg/ml contrasted with the IC50 of the peel extract (556.60 µg/ml). Relative to ascorbic acid, both kiwi extracts have been considerably successful in diminishing hemolysis, thiobarbituric acid reactive substances (TBARS) and GSH levels of AAPH-induced RBCs. Interestingly, with 80 μg/ml, the ethanol peel extract returned the TBARS and GSH levels to the normal level of RBCs (0.022 and 2.86 nmole/mg hemoglobin, respectively).